MEMBENTUK GENERASI ANAK YANG SEHAT, AKTIF, DAN CERIA MELALUI PERILAKU HIDUP BERSIH DAN SEHAT DI SEKOLAH TK KB PERMATA JAYA TAHUN 2026 - Besti Rohana Simbolon; Rameyanti Tampubolon; Rosma Nababan; Dearma Sariani Sinaga; Nazla Rachma Panggabean; Hendrikson R Panjaitan (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2026)
Low awareness regarding Clean and Healthy Living Behavior (PHBS) among early childhood students in the post-pandemic era presents a serious challenge for the partner institution. This multidisciplinary service and research initiative integrates Education (kinesthetic learning methods), Communication (visual campaigns and interpersonal persuasion), and Accounting (financial literacy education and healthy budget accountability) at the Permata Jaya Kindergarten and Early Childhood Education Center (TK KB) in 2026. Key issues faced by the partner included children's lack of independent hygiene practices, monotonous health communication, and the absence of a dedicated budget allocation for school sanitation. Implementation methods involved interactive storytelling, the creation of PHBS visual aids, and guidance on preparing a petty cash budget for sanitation needs. Results demonstrated a dramatic 85% increase in children's understanding of PHBS, a 90% improvement in the effectiveness of health messaging, and the establishment of transparent financial reporting for school sanitation. This multidisciplinary collaboration proved effective in fostering healthy habits among children while simultaneously strengthening the governance of school health facilities.